Personal Security in the Application of Online Software in the Technology Period 4.0 - Danh, Nguyen Tan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Over the three industrial revolutions, man has achieved great achievements. But besides that great success will always go hand in hand with many problems that arise. Because the rate at which technology develops is directly proportional to the threats it poses. The emergence of new technology requires researchers and students to pay attention to discover new threats to make it reliable and user-friendly. In the meantime 4.0 cloud computing is a new technology model. Security issues in cloud computing are considered one of the biggest obstacles besides the broad benefits of cloud computing. New concepts introduced by the cloud create new challenges for the security community. Addressing these challenges requires, in addition to the ability to cultivate and adjust security measures developed for other systems, to propose new security policies, models and protocols to address optimal and effective cloud security challenges. In this article, we provide comprehensive research on cloud security including classification of known security threats and advanced practices in attempting to address these threats. The paper also provides classification dependency and provides solutions in the form of preventive action rather than proactive action.